2001
DOI: 10.1074/jbc.m103007200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Epitope in Cadherin-like Receptors Involved inBacillus thuringiensis Cry1A Toxin Interaction Using Phage Display

Abstract: In susceptible lepidopteran insects, aminopeptidase N and cadherin-like proteins are the putative receptors for Bacillus thuringiensis (Bt) toxins. Using phage display, we identified a key epitope that is involved in toxin-receptor interaction. Three different scFv molecules that bind Cry1Ab toxin were obtained, and these scFv proteins have different amino acid sequences in the complementary determinant region 3 (CDR3). Binding analysis of these scFv molecules to different members of the Cry1A toxin family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
134
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 46 publications
5
134
0
1
Order By: Relevance
“…Cry1Ab crystals were purified by sucrose gradients and protoxin solubilized in 50 mM Na 2 CO 3 (pH 10.5), 0.2% b-mercaptoethanol at 37°C for 2 h [18]. The oligomeric and monomeric forms of Cry1Ab toxin were produced by incubating Cry protoxin for 1 h with scFv73 antibody in a mass ratio of 1:4 and digested with midgut juice (5%) for 1 h at 37°C.…”
Section: Preparation Of Insecticidal Crystal Proteinsmentioning
confidence: 99%
“…Cry1Ab crystals were purified by sucrose gradients and protoxin solubilized in 50 mM Na 2 CO 3 (pH 10.5), 0.2% b-mercaptoethanol at 37°C for 2 h [18]. The oligomeric and monomeric forms of Cry1Ab toxin were produced by incubating Cry protoxin for 1 h with scFv73 antibody in a mass ratio of 1:4 and digested with midgut juice (5%) for 1 h at 37°C.…”
Section: Preparation Of Insecticidal Crystal Proteinsmentioning
confidence: 99%
“…In addition the binding characteristics of this mutant was analyzed, showing that mutant R99E was able to bind to BBMV with similar high affinity as the wild type, since binding competition of biotinylatedCry1Ab toxin with unlabelled mutant protein was identical to that of the unlabelled wild type toxin [21]. Specifically the binding interaction with Bt-R 1 was not affected, since ligand blots and ELISA binding competition assay of the mutant R99E to a Bt-R 1 protein fragment that contains all the Cry1A binding sites characterized so far (CR7 to CR12 ) [14,15,19] showed that it bound to Bt-R 1 protein fragment with the same K D as the wild type Cry1Ab toxin [21]. It is important to mention that the procedure of ELISA competition assay permits the determination of true association rate constants in solution, and several reports have shown agreement in the determination of K D values by these assays and those obtained by conventional methods (immunoprecipitation of the radiolabeled antigen, fluorescence transfer or surface plasmon resonance) [11,12,17].…”
Section: Mutagenesis Of Helix α-3 Of Different Cry Toxinsmentioning
confidence: 88%
“…A synthetic human scFv library-selection of an scFv molecule that mimics a cadherin receptor Our first attempt to characterize the amino acid epitopes involved in the interaction of Cry toxins with their receptor molecules was with the lepidopteran insect Manduca sexta and the Cry1Ab toxin [10]. At that time, two M. sexta proteins that bind Cry1A toxins had been cloned and characterized, a 210 kDa cadherin protein known as Bt-R 1 and a 120 kDa glycosylphosphatidy-linositol (GPI) anchored aminopeptidase N (APN) [21,33].…”
mentioning
confidence: 99%
“…For the panning procedure, we immobilized Cry1Ab toxin in immunotubes and after several panning rounds of selection we identified three scFv-phages that bound specifically to Cry1Ab toxin. Using ligand blots assays and by competing the binding of Cry1Ab toxin with M. sexta brush border membrane vesicles (BBMV) blotted proteins, we identified one scFv (scFv73) that competed the binding of Cry1Ab with the 210 kDa Bt-R 1 molecule but not with the 120 kDa APN [10]. Antibody scFv73 inhibited the toxicity of Cry1Ab toxin in bioassays.…”
mentioning
confidence: 99%
See 1 more Smart Citation